Efektifitas Model Pembelajaran Quantum Learning Dalam Meningkatkan Kecerdasan Emosi Dalam Pembelajaran Bahasa Arab - Tutik Husniati (Kopertais Wilayah III Yogyakarta, 2016)
This study aims to, know, first, the level of emotional intelligence in learning Arabic in MTs N Bantul Kota. Second, know the aspects of emotional intelligence is not optimal emotional intelligence when learning Arabic. Third, determine the effectiveness of the learning model quantum learning to improve emotional intelligence as applied by the practice of learning Arabic in MTs N Bantul Kota. The results of data analysis showed that emotional intelligence of students MTs N Bantul Kota at the time of follow Arabic lessons in control class and experimental class that is well categorized and there was no significant difference between the experimental class and control class. It can be seen also from the data if the pretest scores that get Fhit = 0.020 with probability = 0887 or the acquisition of P > 0.05. Aspects of emotional intelligence are not optimal emotional intelligence after getting treatment learning model of quantum learning when learning Arabic is an aspect of self-regulation and motivation. Categorization on these two aspects are qualitatively the same, either in pre test and at post test, but quantitatively there is an increase but has not been able to change the categorization. The application of methods quantum learning in learning can improve students’ higher emotional intelligence than usual method significantly. From the results of the count get Fhit = 8226 with probability = 0.005. Acquisition p ≤ 0:05 indicates significant. This explains there are significant differences in emotional intelligence of students of the experimental class than control after implementation of methods quantum learning in the experimental class. Emotional intelligence of students in the experimental group x> = 134.18, higher than control x> = 128.16. Based on these results concluded the application of method quantum learning can improve the emotional intelligence of students during the learning of Arabic in MTs N Bantul Kota Academic Year 2014 / 2015.